The one in the middle is the green kangaroo - Blume, Judy.; Aitken, Amy (New York : Dell Yearling, 2004)
Second-grader Freddy hates being the middle one in the family until he gets a part in the school play.
Keywords: Brothers and sisters -- Fiction; Family life -- Fiction; Schools -- Fiction; Theater -- Fiction; Humorous stories